Tracing the photodissociation probability of H2+ in intense fields using chirped laser pulses - Prabhudesai, Vaibhav S.; Lev, Uri; Natan, Adi; Bruner, Barry D.; Diner, Adi; Heber, Oded; Strasser, Daniel; Schwalm, D.; Ben-Itzhak, Itzik; Hua, J. J.; Esry, B. D.; Silberberg, Yaron; et al. (My University, 2010)
The temporal evolution of the dissociation probabilities for various vibrational levels of H2+ is observed in terms of shifts in the kinetic energy release dissociation spectra, induced by linearly chirped intense laser pulses. In contrast to previous observations, in which no dependence on the chirp sign was observed, the energy spectrum reported here shows peak shifts, up for negative chirp and down for positive chirp. For some vibrational levels, dissociation takes place early on in the pulse; hence, care must be taken while interpreting the effect of pulse duration in photodissociation studies. This interpretation is supported by numerical solutions of the time-dependent Schrödinger equation.